Can Right Ventricular Pacing be Useful in the Assessment of Cavo-tricuspid Isthumus Block? - Miracapillo, Gennaro (Indian Heart Rhythm Society, 2008)
BACKGROUND: Cavo-tricuspid isthmus (CTI) block is currently assessed by coronary sinus (CS) pacing or low lateral and septal atrial pacing. Occasionally, CS catheterization through the femoral route can be difficult to perform or right atrial pacing can be problematic because of catheter instability or saturation of the atrial electrograms recorded near the catheter. OBJECTIVES: Our aim was to evaluate the feasibility of assessing cavo-tricuspid isthmus block by means of right ventricular (RV) pacing in patients with ventriculo-atrial conduction, comparing it with CS pacing. METHODS: Circumannular activation was analyzed during CS and RV pacing in consecutive patients in sinus rhythm undergoing CTI ablation for typical atrial flutter. Patients without ventriculo-atrial conduction were excluded from the study. The linear lesion was created during RV pacing and split atrial signals on the ablation line were analyzed. CTI block was confirmed by analyzing local electrograms on the line of block and circumannular activation during CS and RV pacing. RESULTS: Out of 31 patients, 20 displayed ventriculo-atrial conduction (64%) and were included in the study. Before ablation, during RV stimulation, the collision front of circumannular activation shifted counterclockwise in contrast with the pattern observed during CS pacing. After ablation, circumannular activation was similar during CS and RV pacing, showing fully descending lateral right atrium activation, even if double potentials registered on the ablation line were less widely split during RV pacing than CS pacing (111±26 ms vs 128±30 , p=0.0001). CONCLUSIONS: In patients with ventriculo-atrial conduction, tricuspid annulus activation during CS and RV pacing is similar, before and after CTI ablation. The occurrence of split atrial electrograms separated by an isoelectric interval registered on the line of block can be detected during CS or RV pacing. In patients with difficult CS catheterization via the femoral vein, before trying the subclavian or internal jugular route, if retrograde ventriculo-atrial conduction is present, RV pacing can be an easy trick to assess isthmus block.